An Attempt to Create an Automatic Scoring Tool of Short Text Answer in Bahasa Indonesia - Husni Thamrin; Jan Wantoro (IAES Indonesia Section, 2014)
Closed questions offer poor information on student's ability to manage and apply knowledge. On the other hand, open questions have advantages because it may be used to grasp students' conceptual maturity and ability of communication. However, scoring open question answer is not trivial and time-consuming so an automatic scoring tool becomes necessary. An attempt was made to create a scoring tool for open and short text question answer in Bahasa Indonesia that resembles the way school teachers do scoring. Automatic scoring of a student answer was based on the similarity between the answer and predefined key answers. The proposed automatic scoring tool has a form of correlation with human scoring so that the model may be used to predict teacher scoring.